The specificity of emotion dysregulation in adolescents with borderline personality disorder: comparison with psychiatric and healthy controls. Issue 1 (December 2017) - Ibraheim, Marina; Kalpakci, Allison; Sharp, Carla
Abstract Background Research has supported the notion that emotion dysregulation is a core feature of BPD. However, given that this feature is typical of healthy adolescents as well as adolescents with other psychiatric disorders, the specificity of emotion dysregulation to BPD in this age group has not yet been determined. The overall aim of this study was to examine emotion dysregulation in adolescent inpatients with BPD compared with non-BPD inpatient adolescents and healthy non-clinical adolescents, taking into account both global emotion dysregulation deficits and more specific impairments. Method The sample included 185 adolescent inpatients with BPD (M  = 15.23, SD = 1.52), 367 non-BPD psychiatric inpatient adolescents (M  = 15.37, SD  = 1.40), and 146 healthy adolescents (M  = 15.23, SD  = 1.22), all of whom were between the ages of 12 and 17. Borderline personality features were assessed, along with emotion dysregulation and psychiatric severity. Results After controlling for age, gender, and psychiatric severity, results revealed that adolescents with BPD had higher overall emotional dysregulation compared with non-BPD psychiatric controls and healthy controls. These differences were apparent in only two domains of emotion dysregulation including limited access to emotion regulation strategies perceived as effective and impulse control difficulties when experiencing negative emotions. Conclusions Findings suggest BPD-specific elevations on emotion dysregulation generally, and subscales related to behavioral regulation specifically.